A validation of questionnaire information on occupational exposure and smoking. - Pershagen, Göran; Axelson, Olav (Scandinavian Journal of Work, Environment & Health, 1982)
Occupational exposure information obtained via a questionnaire to close relatives of 160 deceased smelter workers was compared with data from employee registers. The data from the questionnaire regarding employment at the smelter had a very high validity, ie, a sensitivity of 98% and a specificity of 99%. When an assessment of arsenic exposure was made from information in the questionnaire, the sensitivity was only 40%, but the specificity was over 90%. Data on smoking habits were available from medical files for only 14 of the subjects. For all 14, the information was identical to the data in the questionnaires. It appears that questionnaires may sometimes be of use for exposure assessments in occupational health epidemiology.
Keywords: arsenic; bias; lung cancer; occupational exposure; questionnaire; register; smelter work; smoking; validation